LITERASI DIGITAL DALAM INFORMASI DAN PEMBELAJARAN MELALUI PENERAPAN DEEP LEARNING - Irwan Maulana; Maharani; Santhi Pertiwi; Lilis Sulistiawati; Nur Bintari, Pramudyasari (Institut Ummul Quro Al-Islami Bogor, 2025)
The Industrial Revolution 4.0 has driven significant transformation in the field of education, particularly through the utilization of digital technology as a learning medium. Digital literacy has become an essential competence for students to effectively absorb, comprehend, evaluate, and create information in a critical and responsible manner. Along with the development of Artificial Intelligence (AI), deep learning technology offers new opportunities to strengthen adaptive and innovative learning processes. This study aims to analyze the contribution of deep learning in enhancing students’ digital literacy, particularly in aspects of information absorption, information creation, evaluation skills, and the promotion of learning creativity. This research employs a qualitative approach using a documentation study method. Data were collected from scientific journals, academic books, reports from educational institutions, and relevant policies. The data were analyzed using content analysis techniques to examine the relationship between digital literacy and the application of deep learning in education. The findings indicate that deep learning can assist students in filtering relevant information, producing creative digital content, receiving accurate automated feedback, and developing creativity and innovation in learning. Nevertheless, the implementation of this technology still faces challenges, including teacher readiness, limited infrastructure, and data security issues. The integration of deep learning in education requires policy support, enhancement of teachers’ digital literacy, and the development of a safe and inclusive learning ecosystem.